117 Predictors of prehospital mortality in patients with major trauma in New Zealand. (20th November 2022) - Montoya, Luisa; Davie, Gabrielle; Kool, Bridget; Dicker, Bridget
Abstract : Background: Major trauma is a significant contributor to morbidity and mortality. The provision of optimal prehospital Emergency Medical Services (EMS) care and timely transfer to advanced-level hospital care are vital to increase the likelihood of survival of following major trauma. The aim of this study was to identify the factors that predict prehospital mortality in New Zealand (NZ) in these patients. Methods: Retrospectively designed prospective cohort study analysing routinely collected data. Individuals of any age attended by an EMS provider in NZ immediately following major trauma between 1 December 2016 and 30 November 2018 were included. Factors predictive of prehospital mortality were explored using modified Poisson regression. Models included patient sociodemographic, triage, injury mechanism, Injury Severity Score (ISS) and geographical location of injury. Results: 3, 334 patients met the eligibility criteria, of which 105 (3.1%) died prehospital. Univariate analysis indicated that Māori ethnicity (RR=1.9; 95%IC: 1.2–3.0) and ISS greater than 24 (RR=16.8; 95%IC: 9.2–30.8) were predictive of prehospital mortality. Multivariable analysis indicated the factors predictive of increased prehospital mortality risks were motor vehicle-related (MV) injury relative to non-MV injury (ARR=4.0; 95%CI: 1.1–14.4) and an ISS greater than 24 relative to those with ISS≤24 (ARR=13.3; 95%CI: 7.2–24.6). Conclusion: Univariate and multivariate analysis showed that high ISS values are strongly predictive of increased prehospital mortality risk. Learning Outcomes: Findings reinforce the need for continued primary prevention efforts and the rapid EMS assessment and management of those with severe injuries in the prehospital setting.